UEFA Euro 2004 tourism impact analysis - Ribeiro, J. Cadima (2004)
The purpose of this paper is exactly to approximate the tourism economic impact of the UEFA Euro 2004 in Portugal. The survey concentrates on the immediate, direct and short-term additional revenue brought into one region by the foreign sport event spectators. One innovating aspect of this paper is the direct data collection on the foreign visitors spending, contouring simulation and forecast problems. Results show an immediate short-term return investment costs generated an immediate and short-term revenue of less than one tenth of the investment costs and overall revenue leakage (or income export) of nearly 325% (50,142 million Euro) of the revenue within the defined regional spatial circuit.